2007
DOI: 10.1002/mame.200700149
|View full text |Cite
|
Sign up to set email alerts
|

EVA Nanocomposites Elaborated with Bentonite Organo‐Modified by Wet and Semi‐Wet Methods

Abstract: EVA copolymer/organoclay nanocomposites were prepared using melt‐compounding. Organoclays were obtained using wet and semi‐wet modification methods. These methods enable us to obtain organoclays with adequate modifier incorporation, but organoclays with a homogeneous and narrow agglomeration size distribution were obtained only with the wet method. TS and EB were higher for nanocomposites obtained with organoclays prepared using the wet method. Analysis of Limiting Oxygen Index, UL94 test and Cone Calorimeter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Two Bragg peaks were observed in the measured range of 2q which correspond to the arrangement of bentonite particles in the EVA matrix. Values of 2q at small angles, and the corresponding interlayer spacing (d 1 ), are presented in Table 2, including the corresponding values for BNT-2M2TH organoclay and EVA/BNT-2M2TH nanocomposite which had been reported previously [15]. The second peaks at higher angles (2q ¼ 4-5 ) are associated with a different type of modifier which produces a smaller interlayer spacing in the bentonite particles.…”
Section: X-ray Diffraction (Xrd) Analysismentioning
confidence: 93%
See 2 more Smart Citations
“…Two Bragg peaks were observed in the measured range of 2q which correspond to the arrangement of bentonite particles in the EVA matrix. Values of 2q at small angles, and the corresponding interlayer spacing (d 1 ), are presented in Table 2, including the corresponding values for BNT-2M2TH organoclay and EVA/BNT-2M2TH nanocomposite which had been reported previously [15]. The second peaks at higher angles (2q ¼ 4-5 ) are associated with a different type of modifier which produces a smaller interlayer spacing in the bentonite particles.…”
Section: X-ray Diffraction (Xrd) Analysismentioning
confidence: 93%
“…The second peaks at higher angles (2q ¼ 4-5 ) are associated with a different type of modifier which produces a smaller interlayer spacing in the bentonite particles. The broad peaks around 2q ¼ 7 are assigned to the initial basal space of the pure BNT indicating that, after the modification process, some parts of the nanoclays remain unmodified [15]. The peaks in the XRD diffractogram and the interlayer spacing achieved showed that intercalated structures may be the main morphology achieved within the organoclay layers in the nanocomposites.…”
Section: X-ray Diffraction (Xrd) Analysismentioning
confidence: 95%
See 1 more Smart Citation
“…This improved fl ame retardance has also been observed in thermoplastic matrix clay nanocomposites. In particular, Cardenas et al [ 13 ] reported the positive effects of the addition of organo-modifi ed synthesized bentonite on the thermal stability and fl ame resistance of EVA, while Dasari et al [ 14 ] reported signifi cant reductions on the heat released of organoclay reinforced polyamide 6.…”
Section: Thermosetting Matrix Nanocompositesmentioning
confidence: 98%
“…This improved flame retardance has also been observed in thermoplastic matrix clay nanocomposites. In particular, Cardenas et al13 reported the positive effects of the addition of organo‐modified synthesized bentonite on the thermal stability and flame resistance of EVA, while Dasari et al14 reported significant reductions on the heat released of organoclay reinforced polyamide 6.…”
Section: Thermosetting Matrix Nanocompositesmentioning
confidence: 99%